Positive Psychology 2.0 in a Foreign Language Classroom: Students’ Emotional Experience in English Classroom Interaction in China - Wang, Yingna; Marecki, Mateusz (Frontiers in Psychology, 2021)
The second wave of positive psychology (PP 2.0) emphasizes how positive and negative psychology complement each other in social contexts. It offers a balanced interactive model that aims at enhancing the optimal learning outcome through the interplay of positive and negative emotions. Building on a large qualitative study of students’ and teachers’ experiences in EFL classrooms in China, this paper argues that adopting the principles of PP 2.0 could facilitate our understanding of learners’ emotional experience in SLA. Using one illustrative case, this paper shows the dynamic and complexity of students’ shifting emotions as they participate in interaction over a span of two months. It is found that the students’ positive emotions could transcend negative emotions and influence their engagement in classroom interaction. This study contributes to the existing research into emotional experiences of classroom interaction that integrates the observable, reflective, and participatory. It draws on interrelated sets of data, including a student and teacher profile questionnaire, classroom observation and recording, student and teacher reflective journals documenting their classroom interaction experiences, and stimulated recall interviews based on recordings and reflective journals. The study in the first place has implications for English teachers and teacher trainers in China and abroad as well as researchers interested in the role of emotional experience in English language learning and teaching.